TikTok Strategies for Nurturing Business Viability for Online Start-Up Sellers in Cebu City Philippines - Campaner, Jonnicko P.; Licayan, Lovely Mae A.; Medecillo, Mary Shielo P.; Soroño, Myca; Villela, Niña Venus (Future Science / FSH-PH Publications, 2025)
This study investigates which of the five TikTok strategies (con-tent format, engagement tactics, hashtag usage, paid advertising, and live streaming) is most effective in driving sales growth, and to provide feasible recommendations in increasing profitability for online start-up sellers and aspiring business owners based on the findings of this study. Addressing the gaps in understanding how TikTok can be effectively utilized by online start-up sellers in Cebu City. This study utilized a quantitative research method and uses the Principle Component Analysis (PCA) to identify the most effec-tive TikTok Strategy in leveraging sales growth. The results reveal that the principal component represents 73.70% of the total vari-ance. The findings revealed that there is a clear indication that all of the five (5) TikTok strategies have an effect in increasing sales growth. The result showed that live streaming is the most effective TikTok strategy, which would boost platform efficiency and en-gagement while paid advertising to be the least effective when it comes to gaining sales growth. These findings contribute to the existing literature by providing insight towards how these factors can affect the sales growth of online sellers or businesses that are utilizing TikTok to market and sell their products and services.